Level of abstraction in parent–child interactions: the role of activity type and socioeconomic status. (23rd January 2020) - de la Rie, Sanneke; van Steensel, Roel C.M.; van Gelderen, Amos J.S.; Severiens, Sabine
Abstract : Background: Various conversational contexts elicit stimulating parent–child interactions to a different degree. Shared reading, a scripted activity, is reported to elicit most abstract speech compared with other activities (e.g., toy play). Parental socioeconomic status (SES) is another key predictor of abstract talk. Shared reading can attenuate differences in abstract speech between SES groups. In the current study, we compared abstraction of parent–child interactions during nonscripted prompting board and shared reading activities. A prompting board is a complex picture around a certain theme, depicting a scenario (i.e., a picture suggesting a sequence of events), and is meant to elicit child speech. Method: We observed 44 parent–child dyads (87% mothers; child M age : 63 months) from various socioeconomic backgrounds during prompting board and shared reading discussions and coded interactions for level of abstraction. Results: Prompting boards were found to elicit both more, and more highly abstract speech (particularly inferencing) than shared reading, and children contributed more often to the conversation. Additionally, most speech on the lowest level of abstraction occurred during prompting boards (e.g., labelling and locating). Shared reading elicited more talk on intermediate levels (e.g., describing aspects of objects and characters and making comparisons to the child's life). Moreover, high‐SES parents and children produced more highly abstract speech and less labelling and locating compared with low‐SES dyads during both activities. Shared reading did not attenuate SES differences in abstract interactions. Conclusions: Prompting boards seem promising for early intervention; however, future intervention studies are needed.